2023
DOI: 10.1002/vetr.2949
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasound features of adrenal lesions in dogs

Abstract: Background The contrast‐enhanced ultrasound (CEUS) features of adrenal lesions are poorly reported in veterinary literature. Methods Qualitative and quantitative B‐mode ultrasound and CEUS features of 186 benign (adenoma) and malignant (adenocarcinoma and pheochromocytoma) adrenal lesions were evaluated. Results Adenocarcinomas (n = 72) and pheochromocytomas (n = 32) had mixed echogenicity with B‐mode, and a non‐homogeneous aspect with a diffused or peripheral enhancement pattern, hypoperfused areas, intralesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Contrast-enhanced ultrasound studies evaluated adrenal gland neoplasia and established parameters for the differentiation of adenoma, adenocarcinoma, and pheochromocytoma [75][76][77][78]. Malignant adrenal gland tumors presented heterogeneous contrast-enhancement patterns.…”
Section: Adrenal Glandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrast-enhanced ultrasound studies evaluated adrenal gland neoplasia and established parameters for the differentiation of adenoma, adenocarcinoma, and pheochromocytoma [75][76][77][78]. Malignant adrenal gland tumors presented heterogeneous contrast-enhancement patterns.…”
Section: Adrenal Glandsmentioning
confidence: 99%
“…Adenomas, adenocarcinomas, and pheochromocytoma shared similar characteristics, such as intra-lesional microcirculation and regions of hypoperfusion. In this way, cytology and histopathology are gold standard methods for confirming the diagnosis [78]. Hypoechoic nodules detected in the hepatic parenchyma during the peak of contrast were highly suggestive of malignancy [73,74].…”
Section: Adrenal Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by evaluation of hemodynamic (image enhancement) patterns, contrast-enhanced POCUS imaging can help identify hepatic arterioportal fistulas ( 92 ). Initial contrast-enhanced POCUS studies also demonstrated improved visualization of tumorous tissue ( 93 ) and could distinguish between benign and malignant lesions ( 94 , 95 ). Given the numerous studies that have detailed a very low incidence of adverse events and the safe use of contrast-enhanced POCUS in animal patients ( 96 98 ), many more diagnostic applications in veterinary medicine could follow.…”
Section: Applications Of Pocusmentioning
confidence: 99%